Barriers to Indonesia's Energy Transition - Nikolaus Loy; Iva - Rachmawati; Sri Issundari; Joko Soesilo (The Indonesian Journal of Planning and Development, 2024)
Considering the energy situation, which can no longer depend entirely on fossil energy, the energy transition is the responsibility of all countries. Indonesia has set a target for renewable technology in 2025 of 23%. However, the share of renewable energy in Indonesia's primary electricity generation will decrease to 10.4% in 2022. This figure further distances the renewable energy mix target and raises doubts among policymakers and energy academics. This article aims to determine the factors that influence the slow energy transition in Indonesia from fossil energy to renewable energy. This article is qualitative research using in-depth interview methods and documentary studies. In-depth interviews were conducted with several technocrats and bureaucrats to find out their views regarding the condition of alternative energy and Indonesia's unpreparedness to the energy transition. Qualitative research shows that the lack of energy justice in policies related to the energy transition causes the slow energy transition. First, complicated bureaucracy and overlapping or contradictory regulations cause procedural justice issues. Second, the unfulfilled distributive justice has led to losses due to policies related to renewable energy for several parties. Third, the country's failure to prioritize the environment caused the unfulfilled restorative justice. Fourth, top-down policymaking led to the field of recognition justice. Fifth, cosmopolitanism justice has yet to be fulfilled because Indonesia has not been able to become a global actor in the issue of renewable energy.